Answer:
The standard from of the expression is:
![(x +1)^2 + (y-1)^2 = (2)^2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lvud2eoj91e85omadt2y59dyd5duuh8n6w.png)
Explanation:
Here the given expression is :
![x^2+2x+y^2-2y=2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/p7fp5ltshd4lqnw76ly0swbmserd6nh716.png)
Now, the standard form of a circle is given as :
![(x-h)^2 + (y -k)^2 = r^2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/xpipjlu4gvezkhnhun5dxq6cecv4mll49h.png)
Here, (h,k) = Coordinates of Center, r = Radius
Also, use the algebraic identity:
![(a \pm b)^2 = a^2 + b^2 \pm 2ab\\](https://img.qammunity.org/2020/formulas/mathematics/middle-school/o3pnnzh2sushxepsqsnczw4xqkucu4x9ws.png)
Now, converting the given expression in the standard form, we get:
![x^2+2x+y^2-2y=2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/p7fp5ltshd4lqnw76ly0swbmserd6nh716.png)
Add 2 on both sides of the equation, we get:
![x^2+2x+y^2-2y +2=2 + 2\\\implies x^2+2x + 1 + y^2-2y + 1 = 4\\\implies (x^2+2x + 1 )+ (y^2-2y + 1) = 4\\\implies (x +1)^2 + (y-1)^2 = (2)^2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/t5k9rwoee218vtrch3kcl4wfbhbphmry83.png)
So, here the standard from of the expression is:
![(x +1)^2 + (y-1)^2 = (2)^2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lvud2eoj91e85omadt2y59dyd5duuh8n6w.png)
Center coordinates here are (h,k) = ( -1 ,1) and Radius = 2 units